The Theatre Guide : a Comprehensive A-Z of the World's Best Plays and Playwrights. - Griffiths, Trevor (A & C Black, 2003)
With over 500 entries on the most important plays and playwrights performed today, from Aristophanes to Mark Ravenhill, this is an authoritative A?Z of contemporary theatre. Stimulating, observant and informative, it is an essential companion for anyone with an interest in drama.